SYSTEMATIC LITERATURE REVIEW DIGITAL MARKETING ANALYSIS OF TIKTOKSHOP APPLICATION FEATURES ON PURCHASING DECISIONS - Fitriani, Lili Karmela; Ramdan, Mohamad; Omar, Abdisamad Abdirahman (Universitas Kuningan, 2025)
The digital era has brought about a significant transformation in the global marketing landscape, with TikTok Shop emerging as an e-commerce platform that integrates creative content with commercial transactions. This study aims to analyze the influence of digital marketing on consumer purchasing decisions on the TikTok Shop platform through a systematic and comprehensive approach. The methodology used is the Systematic Literature Review (SLR) with the PRISMA protocol, analyzing 20 selected journals from the 2019-2024 period obtained from various academic databases such as Google Scholar. The results of the study show that digital marketing elements such as content marketing, influencer marketing, and live streaming have a significant influence on purchasing decisions, with live streaming being the most influential feature. Affiliate marketing has proven to be effective, especially in reaching Generation Z, while several strategies such as flash sales and electronic word of mouth (E-WOM) have shown inconsistent effects. This study concludes that the success of digital marketing on TikTok Shop depends on a holistic approach that integrates various digital marketing elements. It is recommended for business actors to adopt a multi-channel strategy, focus on developing quality content, and utilize the live streaming feature optimally. The TikTok Shop platform needs to continue to refine its features, while further research can explore more deeply the effectiveness of strategies that have not shown significant results